THE INFLUENCE OF KNOWLEDGE AND DISASTER WARNING AND THE PREPARATION OF HIGH SCHOOL STUDENTS IN FACING EARTHQUAKE AND TSUNAMI - Ruri Maiseptya Sari; Hanifah Hanifah; Vike Pebri Giena (Nurse and Health: Jurnal Keperawatan, 2019)
Background: The school community's readiness to face disasters is still considered lacking in Indonesia. Schools as educational institutions are expected to provide an important role for disaster risk education, so students have the provision in dealing with disasters.Objective: This study aimed to identify the factors associated with the preparedness of high school students in dealing with the earthquake and tsunami disasters.Method: This study is analytic survey with cross sectional design. The population in this study were all high school students in Bengkulu City in 2018/2019 academic year. Two stages cluster sampling method have been used in this study. The researcher randomly chooses one high school that will be used as a research location, SMAN 2 Bengkulu City were selected as the result, then the researcher randomly chooses again to determine which class will be the sample, class of XI was chosen with a total of 340 students who spread across 11 classes. The researchers calculated the sample size by using the Slovin formula with the results of 220 respondents. The samples were selected by using proportional random sampling technique, and chosen based on the number of students in each class. Data collection in this study used an instrument in the form of a questionnaire adopted from LIPI consists 65 questions about knowledge and 10 questions about disaster warning and 36 questions about preparedness. The collected data is then processed and analyzed using computer program software and the data were analyzed by using univariate, bivariate and multivariate logistic regression statistical testsResult: The results of this study showed that preparedness of 220 respondents were obtained a mean of 23.57 with a standard deviation of 7.844, knowledge were obtained a mean value of 46.69 with a standard deviation of 8.229, attitudes were obtained a mean value of 60.01 with a standard deviation of 6.210, an emergency response plan were obtained a mean value of 14.95 with a standard deviation of 3.050, and disaster warning were obtained a mean value of 7.19 with a standard deviation of 2.408. Factors related to student preparedness in dealing with disasters were included the level of knowledge (p = 0.020), attitude (p = 0.280), emergency response plan (p = 0.000), disaster warning (p = 0.000).Conclusion: There is a relationship between the level of knowledge, and disaster warnings with disaster preparedness. The most dominant factor in disaster preparedness is disaster warnings. Key words: Preparedness, knowledge, disaster warning.